A comprehensive survey of allergen labeling on pre-packaged food products imported from Mainland China. (May 2021) - Shwe Yee, Nicki; Shao, Qianqian; Uraipong, Chatchporn; Shoji, Masahiro; Lee, Nanju Alice
Abstract: This study investigated the prevalence, type and accuracy of allergen labeling information on 429 imported pre-packaged food products imported from Mainland China sold in Sydney, Australia. Overall, 93.5% of the products complied to the FSANZ's Food Standards Code and included English labels. The 73% of the surveyed products complied with Australian mandatory allergen labeling requirements and stated the presence of allergens in the ingredient lists and allergen summary statements. The 22% of the products contained PAL statements and overall, the wording "may contain traces of" (28.4%) was commonly used. While most PAL statements (69.5%) were in English, a considerable number of PAL statements were only in Chinese (19%). The ELISA analysis revealed that 51.5% of the tested products contained at least one allergen residues, ranging from 0.7 to 297.3 ppm. The 30% of the tested products contained allergen residue levels exceeding the VITAL® Action Level Two (i.e. high risks of allergens) that recommends PAL, where milk (45%) was the most prevalent allergen followed by egg (40%), wheat (35%), and peanut (10%). Among them, 55% did not contain PAL statements and 30% of the positive products with PAL statements contained undeclared allergens (i.e. not specified in the PAL statements). This study deemed 25.8% of the products imported from Mainland China pose potential risks for allergic consumers. This study highlights the necessity of implementing mutually acceptable or harmonized allergen labeling requirements including PAL and risk assessment plans globally. Highlights: 73% of the products from Mainland China complied with the Australian mandatory allergen labeling. 51.5% of products tested contained at least one allergen. 30.3% of products tested were VITAL® Action Level Two products. 55% of VITAL® Action Level Two products did not contain PAL statements. 25.8% pose potential risks for allergic consumers.